MANAJEMEN WAKAF SEBAGAI PEMBIAYAAN BARANG PUBLIK DAN BARANG PUBLIK CAMPURAN DI INDONESIA - Nur Rachmat Arifin (Faculty of Islamic Economics and Business, 2020)
Introduction: This paper is to formulate a model for waqf invested in public goods and mixed public goods in Indonesia. This model is built on understanding the concept of waqf, learning from waqf institutions from the past and present and addressing the problem of perwakafan in Indonesia. Methods: This research uses descriptive qualitative research with library method or library research. This research uses secondary data from the Indonesian Wakaf Agency (BWI), books, journals, newsletters, government reports and websites. Results: Found that a return from the application of invested endowments could help state coffers in the form of public goods and mixed public goods. The overall process can be managed by waqf institutions as waqf nazdir who cooperate in supervising BWI (Badan Wakaf Indonesia) in using government waqf assets need to understand what should be spend required in accordance with syaraih rules. Implications - This research shows how practical waqf can help the Government of Indonesia in financing public goods and mixed public goods. This indirectly indicates an alternative source of funding for these items. The application of waqf concept can learn and adapt from the model developed in this paper. Originality - This paper tries to revive the function of waqf as a provider of public goods and public goods that vary from Islamic history. Inadvertently, this paper also introduces waqf as fiscal policy in Indonesia. Keyword : Waqf, invested endowments, financing public goods and mixed public goods.